2004
DOI: 10.1083/jcb.200402100
|View full text |Cite
|
Sign up to set email alerts
|

F1F0 ATP synthase subunit c is a substrate of the novel YidC pathway for membrane protein biogenesis

Abstract: The Escherichia coli YidC protein belongs to the Oxa1 family of membrane proteins that have been suggested to facilitate the insertion and assembly of membrane proteins either in cooperation with the Sec translocase or as a separate entity. Recently, we have shown that depletion of YidC causes a specific defect in the functional assembly of F1F0 ATP synthase and cytochrome o oxidase. We now demonstrate that the insertion of in vitro–synthesized F1F0 ATP synthase subunit c (F0c) into inner membrane vesicles req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
181
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(194 citation statements)
references
References 47 publications
10
181
2
1
Order By: Relevance
“…43). On the other hand, YidC is required to integrate the AtpH ortholog in bacteria, F o c (44), and it has been suggested that many short membrane proteins with C-terminal signal anchor sequences are posttranslationally integrated by the YidC translocon (45). The degree to which ALB3 (the chloroplast YidC ortholog) participates in the posttranslational integration of plastid-encoded proteins remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…43). On the other hand, YidC is required to integrate the AtpH ortholog in bacteria, F o c (44), and it has been suggested that many short membrane proteins with C-terminal signal anchor sequences are posttranslationally integrated by the YidC translocon (45). The degree to which ALB3 (the chloroplast YidC ortholog) participates in the posttranslational integration of plastid-encoded proteins remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…c-monomers (37). Therefore, it is likely that YidC has an overlapping function with UncI and can complement the UncI deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…YidC is homologous to mitochondrial Oxa1p and Alb3p in chloroplasts, both of which are involved in membrane protein biogenesis (30). It is known that integration of many membrane proteins, including not only M13 procoat and Pf3 coat, but also F0c, CyoA, etc., becomes defective upon YidC depletion (31,32). In in vitro experiments, the integrating nascent chains of membrane proteins are efficiently cross-linked to YidC, confirming that YidC interacts and functions together with SecYEG (33,34).…”
Section: Yidcmentioning
confidence: 81%